Effects of photographer physical attractiveness on photograph aesthetic value assessment. (July 2022) - Zhu, Cui; Liu, Zan; Pei, Meng; Su, Yanjie
Existent studies have demonstrated that being physically attractive leads to preferences and rewards in various scenarios involving performance evaluation. In this study, we explored whether a photographer's physical attractiveness could affect others' assessment of a photograph's aesthetic value. Participants (N = 54 ) accomplished an online task to pair portraits and non-portrait photographs, followed by completing two questionnaires on cognitive reflection and empathy. Analytical results revealed that an attractive photographer was more likely to be associated with a highly aesthetic photograph, and this bias was moderated by the participant's level of cognitive reflection and empathy. Meanwhile, it could be reduced by the participant's professional experience.